MODEL ASESMEN DALAM PEMBELAJARAN BERBASIS KERJA UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN SISWA SMK - Purnamawati, Purnamawati; Sattu, Jacob; Sunardi, Sunardi (Indonesian Journal of Educational Studies, 2010)
Abstract: Work-Based Learning Assessment (WBLA) Model to Improve the Quality of SMK Student. The purpose of this study is to develop students' vocational competency assessment model in the context of work-based learning in the industry that are valid, practical, and effective. Subjects were vocational school students attending Industrial Work Practices (Prakerin), guidance counselor, and instructors at the partner institution (automotive garages) in Makassar. The results show (1) WBLA meets the criteria of validity, effectiveness, and practicality to be applied to work-based learning in industry, (2) the application of WBLA model allows teachers and instructors to assess more objectively the students’ performance (competency), and (3) the application of this assessment model enhances cooperation between schools and industry, particularly in relation to the implementation of competency assessment of students participating in industrial work practices. Abstrak: Model Asesmen dalam Pembelajaran Berbasis Kerja untuk Meningkatkan Kualitas Pembelajaran Siswa SMK. Tujuan penelitian ini adalah mengembangkan model asesmen kompetensi siswa SMK dalam konteks pembelajaran berbasis kerja di industri yang valid, praktis, dan efektif. Subjek penelitian adalah siswa SMK peserta Praktik Kerja Industri (Prakerin), guru pembimbing, dan instruktur pada institusi pasangan (bengkel-bengkel otomotif) di Makassar. Hasil penelitian menunjukkan: (1) Model APBK memenuhi kriteria valid, efektif, dan praktis untuk diterapkan pada pembelajaran berbasis kerja di industry, (2) penerapan Model APBK memungkinkan guru dan instruktur untuk menilai unjuk kerja (kompetensi) siswa lebih objektif, (3) penerapan model asesmen ini dapat meningkatkan kerja sama antara sekolah dan dunia industri, khususnya berkaitan dengan penyelenggaraan asesmen kompetensi siswa peserta prakerin. Kata Kunci: model asesmen, pembelajaran berbasis kerja